2021
DOI: 10.1039/d1ra05026e
|View full text |Cite
|
Sign up to set email alerts
|

Ceria nanorods as highly stable free radical scavengers for highly durable proton exchange membranes

Abstract: Morphology regulation induced high stability of ceria in proton exchange membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…As a result, the redox interplay between Ce 3+ and Ce 4+ persistently transpires over the testing duration of the fuel cell, effectively suppressing radical-induced harm to the membrane. The presence of Ce 4+ on the surface of the nanoparticles also leads to enhanced hydrogen adsorption, which may reduce the fuel crossover through the membrane . The detailed radical scavenging mechanism is illustrated in eqs – normalC e 3 + + OH + H + K normalC e 4 + + H 2 normalO goodbreak0em1em⁣ K = 3 × 10 8 0.25em M 1 0.25em S 1 normalC e 4 + + H 2 O 2 K 1 K 1 normalC e 3 + + OOH + H + goodbreak0em1em⁣ K 1 = 1 × 10 6 0.25em M 1 0.25em S 1 normalC e 4 + + …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As a result, the redox interplay between Ce 3+ and Ce 4+ persistently transpires over the testing duration of the fuel cell, effectively suppressing radical-induced harm to the membrane. The presence of Ce 4+ on the surface of the nanoparticles also leads to enhanced hydrogen adsorption, which may reduce the fuel crossover through the membrane . The detailed radical scavenging mechanism is illustrated in eqs – normalC e 3 + + OH + H + K normalC e 4 + + H 2 normalO goodbreak0em1em⁣ K = 3 × 10 8 0.25em M 1 0.25em S 1 normalC e 4 + + H 2 O 2 K 1 K 1 normalC e 3 + + OOH + H + goodbreak0em1em⁣ K 1 = 1 × 10 6 0.25em M 1 0.25em S 1 normalC e 4 + + …”
Section: Resultsmentioning
confidence: 90%
“…The presence of Ce 4+ on the surface of the nanoparticles also leads to enhanced hydrogen adsorption, which may reduce the fuel crossover through the membrane. 60 The detailed radical scavenging mechanism is illustrated in eqs 7−11…”
Section: K M E a And Ion Conductionmentioning
confidence: 99%
“…Besides, low ceria concentration is essential since the coordination possibility of ceria at the end-side of PEM may create unwanted activity loss. 25 Also, aggregation of ceria at the cathode side of the membrane may increase cell resistance, indicating that ceria immobilization is support-sensitive and thus the design of the support is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, low ceria concentration is essential since the coordination possibility of ceria at the end-side of PEM may create unwanted activity loss. 25 Also, aggregation of ceria at the cathode side of the membrane may increase cell…”
Section: Introductionmentioning
confidence: 99%
“…These reactive oxygen species (ROS) initiate the oxidative decomposition of the polymer membrane; therefore, the in situ removal of the ROS by regenerative radical scavengers can improve the durability and lifetime of the PEMFCs . Previous studies have reported that an addition of ceria nanoparticles (NPs) in the perfluorosulfonated acid (PFSA) membranes, such as Nafion, and the catalyst layer of the membrane electrode assembly (MEA) led to the significant mitigation of the membrane degradation attributed to radical scavenging by the ceria NPs. The radical scavenging properties are reported with various metal oxides, such as ZrO 2 , YSZ, TiO 2 , MnO 2 , and silica-supported Mn, Cr, and Co oxides. , However, cerium oxides and modified cerium oxide materials seem to offer antioxidant properties superior to that of other metal oxides reported in the literature . The regenerative radical scavenging properties of cerium oxides are typically described with the redox cycles between the reduced Ce 3+ and the oxidized Ce 4+ states involving the lattice oxygen vacancies on the surface. , …”
Section: Introductionmentioning
confidence: 99%